1990
DOI: 10.3382/ps.0690045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Presence or Absence of Satellite Chick-Waterers in Conjunction with Nipple-Drinkers on the Mortality and Productive Performance of Broiler Chicks from Young and Old Dams

Abstract: Two runs of one experiment were conducted to study the effects of the presence or absence of satellite (SAT) chick-waterers in conjunction with nipple-drinkers on the mortality and productive performance of mixed-sex, broiler chicks grown to 42 days of age. Data were combined for analysis. The chicks were obtained from dams 29, 31, 61 and 65 wk of age. The treatments were: 1) chicks from 61- and 65-wk-old dams, nipple-drinkers only; 2) chicks from 29- and 31-wk-old dams, nipple-drinkers only; 3) chicks from 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In addition, this inconsistency with their natural behavior (spooning), a study by Heier et al [9] comparing different water supply systems, showed that chicks raised with nipple drinkers had a higher FWM. Carpenter et al [35] compared performance indices in chicks raised with nipple drinkers or with nipple drinkers supported by supplementary drinkers (plate type). They detected that mortality decreased in the latter case.…”
Section: Drip Cupmentioning
confidence: 99%
“…In addition, this inconsistency with their natural behavior (spooning), a study by Heier et al [9] comparing different water supply systems, showed that chicks raised with nipple drinkers had a higher FWM. Carpenter et al [35] compared performance indices in chicks raised with nipple drinkers or with nipple drinkers supported by supplementary drinkers (plate type). They detected that mortality decreased in the latter case.…”
Section: Drip Cupmentioning
confidence: 99%
“…Peterson et al (1986), in a preliminary study, found that starting day-old broiler chicks might require additional water from supplemental chick waterers in addition to mat supplied by nipples. Carpenter et al (1990) found that the livability of broiler chicks started with supplemental waterers in addition to nipple waterers was greater than that of broilers started on nipple waterers alone.…”
Section: Introductionmentioning
confidence: 85%